CONFIGURATION SOFTWARE FOR PACKET RADIO DATA COMMUNICATION - Vincentsius Surya; Dra. Hj. Latifah. MM Dra. Hj. Latifah. MM (Jurnal Sistem Informasi, 1997)
In the normal course of communication, the NOS system may communicate withpacket data communication system of another. This is because all systemscommunicating using the protocol AX.25 (Amateur X.25), which is a variant of X.25,shown for packet radio communications.Communication has not been so perfectly executed. There are still many problemsthat arise. This is because communication is carried out using HT communication toolthat has little power. Besides having a lot of interference, the communication can notreach remote areas to get a wave of other radio BBS server.